Photogrammetry low-cost for geotechnical centrifuge modelling test - A. Cardaci; D. Giretti; P. Azzola (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The buildings design is based on a thorough geotechnical study. Knowing the physical and mechanical properties of soils and rocks is a must for engineering calculations. The stability of the building and the lives of people are at risk if the relationship between the structure and the ground is not understood. Geotechnical centrifuges can be used to test physical models for geomeccanics characterization of the land. The first Italian centrifuge - still the only one active in Italy - is that of the former Istituto Sperimentale Modelli e Strutture (ISMES), now Istituto Sperimentale Modelli Geotecnici (ISMGEO). The elastoplastic properties of the soil can be estimated by observing the movement of critical points during the acceleration test. This is possible with traditional transducers, but also thanks to Close Range Multiview Photogrammetry, which allows you to return the digital model of the test before and after the test. By comparing the two models, target displacements can be evaluated, slope surfaces can be measured, and the steepest angle of descent can be determined. Additionally, the study of surface normals enables the identification of the degree of depression and the curved characteristics of the ground, such as anticlinal and synclinal. The contribution focuses on the experiences and outcomes obtained through digital photogrammetry during tests carried out for the SFARS project (Seismic FAilure and post-failure Response of Slopes) funded by the Ministero dell’Istruzione, dell’Università e della Ricerca (MIUR) for the Research Project of National Interest (PRIN 2022).